Use of Astronomy as a tool to improve gender balance in Tertiary Institutions - Jurua, Edward (IAU General Assembly, 2024)
The number of women in the science discipline is still low in Uganda. In the case of Mbarara University of Science and Technology (MUST), the percentage of bachelor degrees going to ladies in physics and mathematics is about 7%, while for chemistry and biology it is close to 15%. This is a very small percentage which needs to be increased. There is evidence that culture has a large influence on the participation of women in Sciences. In order to change this perspective about pursuing science careers, we organised a number of activities, which included visits to selected secondary schools, Universities and other institutions to investigate the climate for girls/women, to catalogue the problems that they face, and to suggest improvements that could be made. We present our findings in this paper
Keywords: Gender balance; Astronomy; Tertiary Institutions